A SIW‐DGS wideband bandpass filter with a sharp roll‐off at upper stopband. Issue 4 (April 2017) - Liu, Chao; An, Xiang
ABSTRACT: In this article, a wideband bandpass filter is proposed, which combines substrate integrated waveguide (SIW) with four improved dumbbell defected ground structure (DGS) cells. The novel DGS, as a resonator on the metal ground, can produce two transmission zeros, aiming to improve the frequency selectivity and extend the upper stopband. The roll‐off at the upper side is extremely sharper (about 58 dB/GHz). Therefore, the filter shows advantages in terms of the compact size, stopband rejection, good bandpass, and high frequency selectivity. The filter was fabricated and measured. The measured 3 dB bandwidth is from 6.85 to 11.11 GHz, representing a fractional bandwidth of 47.4% at a center frequency of 8.98 GHz. Within the passband, the insertion loss is 1.5 dB and the return loss is better than 18 dB, including the loss from two SMA connectors. The measured results and simulation results are in good agreements. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:789–792, 2017